PERAN AKSESIBILITAS DALAM MENDUKUNG KEPUASAN PENGUJUNG DI OBJEK WISATA ALAM CURUG NGEBUL [The Role Of Accessibility In Supporting Visitor Satisfaction At The Natural Tourism Object Of Curug Ngebul] - elsa_dwitiyana; Wildan Rizky Rahadian (Bogor Hospitality Journal, 2025)
The background of this research is based on the significance of accessibility as a key factor influencing tourist experience and satisfaction, in addition to the natural attractions offered by Curug Ngebul. This study aims to analyze the role of accessibility in supporting visitor satisfaction at the Curug Ngebul natural tourism site, Cianjur Regency. Employing a quantitative approach with a descriptive design, data were collected through field surveys using questionnaires distributed randomly to visitors. The variables analyzed include ease of access, road conditions, availability of transportation, signage, and distance from the city center. The results indicate that good accessibility has a positive effect on visitor satisfaction, particularly in terms of travel comfort, ease of reaching the location, and the availability of supporting information and facilities. These findings emphasize that improving accessibility can be an effective strategy to increase both the number of visits and visitor satisfaction.